HUBUNGAN AGAMA ISLAM DAN PEMBANGUNAN EKONOMI DALAM KEMAJUAN NEGARA: SEBUAH TINJAUAN UMUM - Restu Prana Ilahi; Indra Ramdhani; Muhamad Yusuf; Doli Witro (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2022)
Abstract:This article discusses the relationship between religion and economic development. Both have in common in achieving a goal, namely the creation of prosperity in human life. It was initiated by the findings of Weber, who observed the behavior of Catholics and Protestants who have differences in carrying out their lives. Protestants who take advantage of the economic side in their lives make them superior to Catholics. So that an initiative emerged to carry out church reform based on the arbitrariness of the Catholic church in carrying out rites that were more used for personal interests. Through a set of rules, Islam allows and even encourages a Muslim to carry out development, especially economic development. Because as a caliph on this earth, humans are obliged to take care of, preserve, and maintain various things in this universe, and it is forbidden to destroy them. In Islamic teachings, five points form the basis of human life to achieve prosperity, namely religion (ad-din), soul (an-nafs), reason (al-aql), offspring (nasb), and property (mal). Economic development in the Islamic point of view is raised, one of which is to achieve prosperity through these five main elements. So, in this case, religion has a close relationship with aspects of economic development, as can be seen from the similarities between the two in achieving the welfare of human life.Abstrak: Artikel ini membahas hubungan antara agama dan pembangunan ekonomi. Keduanya memiliki kesamaan dalam mencapai suatu tujuan, yaitu terciptanya kesejahteraan dalam kehidupan manusia. Hal ini diawali dengan temuan Weber yang mengamati perilaku umat Katolik dan Protestan yang memiliki perbedaan dalam menjalankan kehidupannya. Orang Protestan yang memanfaatkan sisi ekonomi dalam hidupnya menjadikan mereka lebih unggul dari Katolik. Sehingga muncul inisiatif untuk melakukan reformasi gereja berdasarkan kesewenang-wenangan gereja Katolik dalam menjalankan ritus-ritus yang lebih banyak digunakan untuk kepentingan pribadi. Melalui seperangkat aturan, Islam membolehkan bahkan mendorong seorang muslim untuk melakukan pembangunan, khususnya pembangunan ekonomi. Karena sebagai khalifah di muka bumi ini, manusia wajib menjaga, memelihara, dan memelihara berbagai hal yang ada di alam semesta ini, dan dilarang untuk dimusnahkan. Dalam ajaran Islam, lima hal yang menjadi landasan hidup manusia untuk mencapai kesejahteraan, yaitu agama (ad-din), jiwa (an-nafs), akal (al-aql), keturunan (nasb), dan harta (mal). Pembangunan ekonomi dalam pandangan Islam dimunculkan, salah satunya untuk mencapai kesejahteraan melalui lima unsur utama tersebut. Jadi, dalam hal ini agama memiliki hubungan yang erat dengan aspek pembangunan ekonomi, terlihat dari persamaan keduanya dalam mencapai kesejahteraan hidup manusia.